Incidence of breakthrough fungal infections on isavuconazole prophylaxis compared to posaconazole and voriconazole. Issue 2 (1st March 2023) - Scott, Sara A.; Perry, Cory; Mahmoudjafari, Zahra; Martin, Grace A.; Boyd, Samuel; Thompson, Jeffrey; Thomas, Beth
Abstract: Background: Invasive fungal infections (IFIs) are a common infectious complication during the treatment of acute myeloid leukemia (AML), high‐risk myelodysplastic syndrome (MDS) or post hematopoietic cell transplantation (HCT). For these patients, the National Comprehensive Cancer Network recommends posaconazole or voriconazole for IFI prophylaxis. In clinical practice, however, there has been increased use of isavuconazole due to favorable pharmacokinetic and pharmacodynamic parameters despite limited data for this indication. The comparative prophylactic efficacy of antifungals in this patient population has not been reported, and an analysis is warranted. Methods: This retrospective, matched cohort, single‐center study, included AML, MDS, or HCT patients who began treatment or underwent transplant between January 1, 2015 and July 31, 2021. Isavuconazole patients were matched 1:2 with patients receiving posaconazole or voriconazole prophylaxis. Results: A total of 126 patients were included, 42 received isavuconazole, 81 received posaconazole, and three received voriconazole. The majority of patients were male receiving secondary IFI prophylaxis while receiving steroids for treatment of GVHD. The incidence of possible, probable or proven IFI was 16.7% in the isavuconazole group compared to 10.7% in the posaconazole and voriconazole group (OR 1.28, 95% CI −0.9–1.4; p = .67). Hepatotoxicity occurred in 16 total patients, 14 receiving posaconazole and two receiving isavuconazole. Conclusion: Patients who received isavuconazole prophylaxis during AML induction therapy or post‐HCT experienced a similar incidence of breakthrough fungal infections compared to those who received posaconazole or voriconazole. These results suggest no difference in antifungal prophylactic efficacy; however larger prospective comparative studies are needed. Abstract :